Electronic changes at the Pt(1 1 1) interface induced by the adsorption of OH species - Arce, Mauricio Damián (2012)
We perform a detailed analysis of the modifications in the electronic properties when an OH radical adsorbs on Pt(1 1 1). On the basis of first principle calculations, we provide an overview of the interface at the atomic level at low coverages (1/9 of a monolayer). The electronic factors that govern the adsorption phenomenon are discussed. The interaction of the electronic states involved in the bond formation is investigated. In this context, we examine the charge redistribution and the projected density of states onto the different participating atoms and orbitals. We establish a comprehensive picture which provides a valuable guideline to understand the complicated interplay of the electronic states in the formation of bonds.